A strategy for controlling Hypervirulent Klebsiella pneumoniae: inhibition of ClpV expression - Wenke Liu; Dan Wang; Qiangxing He; Shiwen Cao; Jiaxin Cao; Huajie Zhao; Junwei Cui; Fan Yang (BMC Microbiology)
Abstract The emergence and prevalence of hypervirulent Klebsiella pneumoniae (hvKP) have proposed a great challenge to control this infection. Therefore, exploring some new drugs or strategies for treating hvKP infection is an urgent issue for scientific researchers. In the present study, the clpV gene deletion strain of hvKP (ΔclpV-hvKP) was constructed using CRISPR-Cas9 technology, and the biological characteristics of ΔclpV-hvKP were investigated to explore the new targets for controlling this pathogen. The results showed that clpV gene deletion did not affect the growth ability of hvKP. However, knocking out the clpV gene markedly decreased the mucoid phenotype and the biofilm formation ability of hvKP. It reduced the interspecific competition of hvKP with Escherichia coli, Salmonella, Pseudomonas aeruginosa, and Staphylococcus aureus. The clpV deletion significantly changed the transcriptome profile of hvKP, inhibited the expression of virulence factors, and decreased the lethality of hvKP against Galleria mellonella larvae. In vitro experiments showed that lithocholic acid could inhibit the expression of the clpV gene and reduce the virulence of hvKP. Our data suggested that the clpV gene may be a potential target for decreasing hvKP infection risk.